2013
DOI: 10.1902/jop.2013.120594
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant Analysis for the Thin Periodontal Biotype Based on the Data Acquired From Three‐Dimensional Virtual Models of Korean Young Adults

Abstract: PLSum5 >24 mm is the suggested criterion for identifying high-risk thin biotype patients based on the comparison with the results from gingival transparency inspection. A clinical reevaluation of this criterion should be examined in additional studies for application in real clinical situations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 24 publications
(43 reference statements)
6
30
0
1
Order By: Relevance
“…A recent study suggested that if the sum of the lengths of the five papillae from maxillary canine to canine is >24 mm, the patient may be considered as having a thin biotype. 13 Although interesting, these data remain to be confirmed and have yet to gain clinical acceptance.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study suggested that if the sum of the lengths of the five papillae from maxillary canine to canine is >24 mm, the patient may be considered as having a thin biotype. 13 Although interesting, these data remain to be confirmed and have yet to gain clinical acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, other studies have considered gingival biotype as a patient-specific factor. [12][13][14] A recent study by Cook et al 16 suggested that the periodontal biotype (thick or thin) at a patient level does translate into specific site-level factors, including probe visibility, papilla height, width of KT, and distance from the cemento-enamel junction (CEJ) to the alveolar crest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…치은을 통해 치주탐침자의 외형이 비치면 "얇은" 생체형(thin biotype)으로, 비치지 않으면 "두꺼운" 생체형"(thick biotype)으로 분류하였다. [23][24][25] 개인의 치은 생체형은 양 중절치에서 모두 치주탐침 자가 비치는 경우는 "얇은" 생체형으로, 그렇지 않은 경 우는 "두꺼운" 생체형으로 구분하였다. Table 1, 2).…”
Section: 치은 생체형 결정unclassified